Properties of the volume phase in the layerwise growth - Brodskii, R.; Tur, A.V.; Yanovsky, V.V. (Functional Materials, 2014)
Assuming statistical properties of phases in the layer are specified, some properties of the volume phase permeating many layers studied. In this paper, we consider analytically the case of one island in the layer and numerically the case of larger and a random number of islands of other phase. The distribution function of the phases overlapping area is obtained. Universal behavior of the distribution function in the small-scale field is established.